Performance evaluation of organic emulsion liquid membrane on phenol removal - Ng, Y.S.; Jayakumar, N.S.; Hashim, M.A. (Elsevier, 2010)
The percentage removal of phenol from aqueous solution by emulsion liquid membrane and emulsion leakage was investigated experimentally for various parameters such as membrane:internal phase ratio, membrane:external phase ratio, emulsification speed, emulsification time, carrier concentration, surfactant concentration and internal agent concentration. These parameters strongly influence the percentage removal of phenol and emulsion leakage. Under optimum membrane properties, the percentage removal of phenol was as high as 98.33%, with emulsion leakage of 1.25%. It was also found that the necessity of carrier for enhancing phenol removal was strongly dependent on the internal agent concentration.